Медіасередовище у формуванні медіакомпетентності майбутніх лікарів - Мурзіна, Олена Анатоліївна; Murzina, O. A. (My University, 2025)
У статті розглянуто медіасередовище у формуванні медіакомпетентності майбутніх лікарів у процесі доклінічної професійної підготовки в медичному університеті. Розглянуто основні поняття “медіасередовище”, “медіапростор” та “освітнє середовище”. Медіасередовище закладу вищої медичної освіти розглянуто як комплекс систематизованих сучасних освітніх ресурсів із належним методичним, технологічним і технічним супроводом. Виокремлено важливі функції медіасередовища. Популяризуються медіатехнології в освітньому процесі закладу вищої медичної освіти з метою актуалізації їх використання у процесі доклінічної професійної підготовки сучасного лікаря. The article highlights issues related to the media environment as a factor in the development of media competence of future doctors in the process of preclinical professional training at a medical university. The basic concepts of “media environment”, “media space”, and “educational environment” are considered. Important functions of the media environment are highlighted. Media technologies are popularized in the educational process of a higher medical education institution in order to actualize their usage in the process of preclinical professional training of a modern doctor. It is noted that the formation of media competence of future doctors requires the creation of both digital and non-digital media environment of a higher medical education institution, which is adequate to the current requirements for adapting the educational process to changes in society under conditions of general digitalization and professional activity of future doctors. The media environment of a higher medical education institution is considered as a complex of systematized modern educational resources with proper methodological, technological and technical support, which provides conditions for the organization and implementation of the educational process, its management and its quality at all educational levels. The article proves that the media environment is a certain system of influences and conditions which ensures high-quality professional training of healthcare professionals. Therefore, when creating a media environment, all objective and subjective possibilities of the educational process of preclinical professional training at a medical university are taken into account. This approach allows the components of the educational space to perform the function of a factor that influences the development of professional qualities of the future specialist. Therefore, taking into account its features, it is possible to exert an indirect influence on the educational process and its results. It is proved that the creation of a common media environment of a higher medical education institution if based on the integration of media information on electronic media, media technologies of interaction, which unites digital libraries, electronic resources, media materials, structured electronic training courses used in the educational process will contribute to the development of media competence of future doctors.
Media environment in the formation of media competence of future doctors
Keywords: медіа компетентність; медіа середовище; медіапростір; освітнє середовище; медіа технології; цифровізація; media competence; media environment; media space; educational environment; media technologies; digitalization